2020
DOI: 10.1007/s12686-020-01128-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TaqMan qPCR protocol for detecting Acipenser ruthenus in the Volga headwaters from eDNA samples

Abstract: A recent eDNA-metabarcoding study assessing fish diversity in the Upper Volga catchment did not detect sterlet at any of the sampled stretches, despite recent sightings that suggest its presence. We designed a TaqMan qPCR protocol to test for sterlet in selected eDNA samples from that study. In-silico and in-vitro tests confirm the protocol's high sensitivity and specificity to sturgeon taxa and potentially paddlefishes. Using this assay, sterlet were not detected in 26 eDNA samples from the Volga headwaters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…These results are concordant with previous studies that showed a higher sensitivity of targeted qPCR compared to metabarcoding (Bylemans et al, ; Harper et al, ), indicating a better performance of targeted approaches particularly for species of low abundance. However, a recently developed TaqMan qPCR assay did not detect sterlet ( Acipenser ruthenus ) in the same system, despite recent reports of its presence at individual sites (Schenekar, Schletterer, & Weiss, ), potentially indicating the border of sensitivity of such assays for a species occurring at very low densities. The sensitivity of eDNA assays will always be influenced by the filtered water volume, storage and extraction methods, and the number of PCR replicates performed, as well as both metabarcoding thresholds or qPCR detection thresholds (as also discussed by Goldberg et al, ; Harper et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…These results are concordant with previous studies that showed a higher sensitivity of targeted qPCR compared to metabarcoding (Bylemans et al, ; Harper et al, ), indicating a better performance of targeted approaches particularly for species of low abundance. However, a recently developed TaqMan qPCR assay did not detect sterlet ( Acipenser ruthenus ) in the same system, despite recent reports of its presence at individual sites (Schenekar, Schletterer, & Weiss, ), potentially indicating the border of sensitivity of such assays for a species occurring at very low densities. The sensitivity of eDNA assays will always be influenced by the filtered water volume, storage and extraction methods, and the number of PCR replicates performed, as well as both metabarcoding thresholds or qPCR detection thresholds (as also discussed by Goldberg et al, ; Harper et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…trammel‐nets). Recent advances in environmental DNA (eDNA) suggest that this method can be used in future for monitoring the sturgeon populations in large rivers (Pfleger et al, 2016; Schenekar, Schletterer & Weiss, 2020) such as the Danube.…”
Section: Discussionmentioning
confidence: 99%
“…However, these primers are not able to distinguish among Ponto-Caspian species, namely the Siberian and Russian sturgeons, and sterlet (Knudsen et al, 2022). Schenekar et al (2020) developed an assay for A. ruthenus and possibly Huso, but this also amplified other non-target sturgeons. According to the approach proposed by Farrington and Lance (2014), positive detection of North American species using common markers, in combination with the absence of positive detection by species-specific markers, makes it possible to determine the occurrence of other sturgeon species with an overlapping range.…”
Section: Status In Kazakhstanmentioning
confidence: 99%